Implementasi Kebijakan Program Merdeka Belajar Pada SMA Negeri 1 Kualuh Hulu Kabupaten Labuhan Batu Utara Provinsi Sumatra Utara - Hendrik Siahaan; Nina Angelia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the implementation of the Freedom of Learning policy at SMA Negeri 1 Kualuh Hulu, Labuhan Batu Utara Regency, using the George Edward III policy implementation theory approach, which includes communication, resources, disposition, and bureaucratic structure. The research method used is qualitative descriptive, with data collection techniques through in-depth interviews, observations, and documentation. The results of the study show that communication between principals, teachers, and students has been going well, supporting the understanding of this policy at the school level. Teachers are highly motivated to implement more flexible teaching methods, but challenges arise from students' readiness to learn independently. In addition, the main obstacles in the implementation of Merdeka Learning are limited technological facilities, internet access, and lack of an effective evaluation system. Therefore, further support is needed from the government in providing digital facilities, teacher training, and strengthening the evaluation mechanism so that this policy can be implemented optimally and sustainably.